Queer identities and marginalization in East and Southeast Asia: promoting SDG5 gender equality and LGBTQ+ rights - Wenxiao, Sun; Abdullah, Karmilah; Yee, Sharon Ong Yong (Editora Alumni In, 2024)
Objective: The aim of this study is to compare and analyze the identity construction and marginalization of LGBTQ+ communities in East and Southeast Asia, with a specific focus on tomboys and transgender women. Theoretical Framework: Grounded in Queer Theory and Cognitive Dissonance Theory, the research explores how cultural, social, and political factors influence self-identification and mental health within these groups. Method: A mixed-methods approach, incorporating a literature review and cross-cultural comparison, was employed, covering countries such as China, South Korea, Japan, Malaysia, Singapore, and Thailand. Results and Discussion: The findings reveal that cultural context, government policies, and religious beliefs significantly impact visibility and social acceptance of LGBTQ+ individuals. The discussion highlights the importance of supportive legal frameworks and mental health resources to address marginalization. Research Implications: The study contributes to the understanding of LGBTQ+ identities in East and Southeast Asia, offering policy recommendations that align with SDG 5 (Gender Equality). Originality/Value: This research is one of the few studies providing a cross-cultural perspective on tomboy and transgender female identity construction in East and Southeast Asia, making it valuable for future policy development and mental health support initiatives.